By Youth, for Adults: Categorizing 100 Watt Productions' Ecocentric Applied Theatre Methodologies - Venner, Matthew (Université d'Ottawa / University of Ottawa, 2022)
This thesis project explores the evolving relationship between Applied Theatre and youth-led environmental activism in Canada. It uses Ottawa-based 100 Watt Productions as its primary case-study, locating the company's performance history, creation methodologies, and pedagogy within English Canada's recent Applied Theatre and Theatre for Young Audiences (TYA) landscapes. This analysis is accomplished through a mixture of textual analysis, performance analysis, and interviews with the company's founder, Kristina Watt Villegas. Particular focus is placed on Watt's approach to collaborating with young people on 12, the company's most recent theatrical production and most urgent call for climate action to date, having toured theatres, schools, board rooms, and government offices across Canada’s capital region. 12 is composed of a mixture of brief vignettes, poetic compositions, and verbatim excerpts regarding climate crises, described as a "cross-generation love story - a playful theatrical invitation [...] to stop, listen, and to consider what it actually means to take action at this point" (Watt, "Creations: 12"). This thesis project proposes that productions such as these demand a new subcategorization of Applied Theatre, formulated here as Youth Theatre for Adult Audiences (YTAA). This YTAA terminology describes Applied Theatre that has been specifically created by young people for adults, a performance dynamic that has proven to be particularly well suited to the unprecedented political challenges faced by our youngest generations, not only in its compatibility with the platforming of climate appeals, but also in its unique capacity to elevate those young voices through a reframing of the aesthetic experience, often incorporating the participants' own creation process into the audience's overall consideration of aesthetic experience. In this sense, 12 acts as a microcosm for YTAA's escalating significance as an Applied Theatre subcategory, pointing towards an urgent need for increased attention, both in Canadian theatre criticism and scholarship more broadly.
Keywords: Applied Theatre; TYA; Ecodramaturgy; Political theatre; YTAA; Environmentalism; Youth activism; Climate action